Strategies for fighting pandemic virus infections: Integration of virology and drug delivery - Nakamura, Takashi; Isoda, Norikazu; Sakoda, Yoshihiro; Harashima, Hideyoshi (Journal of controlled release, 2022)
Respiratory viruses have sometimes resulted in worldwide pandemics, with the influenza virus and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) being major participants. Long-term efforts have made it possible to control the influenza virus, but seasonal influenza continues to take many lives each year, and a pandemic influenza virus sometimes emerges. Although vaccines for coronavirus disease 2019 (COVID-19) have been developed, we are not yet able to coexist with the SARS-CoV-2. To overcome such viruses, it is necessary to obtain knowledge about international surveillance systems, virology, ecology and to determine that immune responses are effective. The information must then be transferred to drugs. Delivery systems would be expected to contribute to the rational development of drugs. In this review, virologist and drug delivery system (DDS) researchers discuss drug delivery strategies, especially the use of lipid-based nanocarriers, for fighting to respiratory virus infections. [Display omitted] •The virology and ecology of pandemic viruses are comprehensively reviewed.•Strategies that are jointly developed by virologists and DDS researchers.•Lipid nanoparticle mediated innate boosters for preventing unknown pandemic virus.•Potentially safe live artificial vaccines containing a universal antigen.